Θ‐ϕ‐Contraction on α, η‐Complete Rectangular b‐Metric Spaces. (1st August 2020) - Kari, Abdelkarim; Rossafi, Mohamed; Marhrani, El Miloudi; Aamri, Mohamed
Abstract : In this paper, we present some fixed point results for generalized θ ‐ ϕ ‐ contraction in the framework of α, η − compete rectangular b ‐ metric spaces. Further, we establish some fixed point theorems for this type of mappings defined on such spaces. Our results generalize and improve many of the well-known results. Moreover, to support our main results, we give an illustrative example.